Fibre type-dependent response of broiler muscles to dietary antioxidant supplementation for oxidative stability enhancement. Issue 6 (1st November 2016) - Delles, R. M.; True, A. D.; Ao, T.; Dawson, K. A.; Xiong, Y. L.
ABSTRACT: The influence of dietary antioxidants and quality of oil on the oxidative and physico-chemical properties of chicken broiler breast and thigh meat stored was studied in either an oxygen-enriched (HiOx: 80% O2 /20% CO2 ) or an air-permeable polyvinylchloride (PVC) packaging system during retail display at 2–4°C for up to 14 and 7 d, respectively. Broilers were fed on a diet with either a low-oxidised (peroxide value (POV) 23 meq O2 /kg) or a high-oxidised (POV 121 meq O2 /kg) oil, supplemented with or without an algae/selenium-based antioxidant with organic minerals, for 42 d. Lipid and protein oxidation, myofibrillar protein profile and purge loss were analysed. In both packaging systems, lipid oxidation (thiobarbituric acid-reactive substances [TBARS]) was inhibited by up to 65% and 57% in chicken breast and thigh, respectively, with an antioxidant-supplemented diet compared to those without. In both breast and thigh samples, protein sulfhydryls and water-holding capacity (purge loss) were better protected by the antioxidant dietary treatment, regardless of oil quality. Thigh muscles had up to sevenfold greater TBARS formation and more myosin heavy chain losses compared to breast samples. Antioxidant supplementation was more protective against lipid oxidation and water-holding capacity in the group fed on high-oxidised oil compared to those fed on low-oxidised oil. The results suggest that dietary antioxidants can minimise the negative impact of oxidised oil on broiler meat quality, and this protection was more pronounced for thigh than breast muscle, indicating inherent variations between muscle fibre types.